2017
DOI: 10.3892/etm.2017.5172
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits the development of non‑small cell lung cancer by inhibiting autophagy and apoptosis

Abstract: Abstract. Among patients with primary lung cancer, 75-80% present with non-small cell lung cancer (NSCLC). However, there is a lack of studies into the potential preventive effects of curcumin against the activation of autophagy in NSCLC. Therefore, the present study primarily focused on the protective role of curcumin in NSCLC. It was demonstrated that curcumin decreased the viability of the human lung cancer cells lines, A549 and H1299, in a time-and dose-dependent manner (P<0.05). Treatment with curcumin al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…It has been reported to exhibit extensive pharmacological activity, with anti-inflammatory, antioxidative, and antitumor properties. In recent years, several studies have investigated the antifibrotic effects of curcumin on organs such as the liver and kidney [11, 2629]. However, thus far, no accounts of curcumin use for joint contracture have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to exhibit extensive pharmacological activity, with anti-inflammatory, antioxidative, and antitumor properties. In recent years, several studies have investigated the antifibrotic effects of curcumin on organs such as the liver and kidney [11, 2629]. However, thus far, no accounts of curcumin use for joint contracture have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin was shown to inhibit PI3K/Akt/mTOR pathways in NSCLC cells A549 [118] and H1299 [119]. The findings demonstrated that curcumin treatment suppresses the PI3K/Akt/mTOR pathway by decreasing the Akt and mTOR phosphorylation thus inducing apoptosis [119,120].…”
Section: Phosphatidylinositol-3-kinase-akt-mtor (Pi3k/akt/mtor)mentioning
confidence: 90%
“…Curcumin was shown to inhibit PI3K/Akt/mTOR pathways in NSCLC cells A549 [118] and H1299 [119]. The findings demonstrated that curcumin treatment suppresses the PI3K/Akt/mTOR pathway by decreasing the Akt and mTOR phosphorylation thus inducing apoptosis [119,120]. On a different note, a tumor suppressor phosphatase and tensin homolog (PTEN) protein has been found to inactivate PI3K/Akt/mTOR pathways through dephosphorylation of PIP 3 to PIP 2 [121].…”
Section: Phosphatidylinositol-3-kinase-akt-mtor (Pi3k/akt/mtor)mentioning
confidence: 98%
“…Further investigations confirmed that curcumin (40 µM) triggered autophagy in A549 cells through the activation of the AMPK signaling pathway, an increase in gene expression levels of human ganglioside (GD)-3 synthase (hST8Sia I) and of its catalyzed protein product GD [ 206 ]. Similarly, Wang et al reported that curcumin (10 µM) inhibited the growth of other NSCLC cells (H1299; A549), it suppressed PI3K/Akt/mTOR activation and thus it induced apoptosis and autophagy [ 207 ]. Moreover, curcumin (15 µM) enhanced the autophagy induced by galbanic acid (40 µM), a sesquiterpene coumarin in NSCLC A549 cells.…”
Section: In Vitro- and In Vivo-mediated Autophagy By Polyphenolsmentioning
confidence: 99%